The emergence and topicality of the “ecological-environmental” problem: a critical approach from the Decoloniality of Power - López Córdova, Dania (2019)
This article aims to conduct a critical review of how the "ecological / environmental" problem has been built since the seventies of the last century. From a dominant perspective, the theoretical approach to ecological conflicts has been largely carried out without considering various relations of power, causing this problem to be analyzed only from an environmental perspective, and from an anthropocentric and instrumental point of view. This mainstreaming perspective has tried in vain to reconcile economic growth or capitalist accumulation with environmental and social balances, with a view to achieving "development" without challenging the contradictions of capitalism. From critical approaches, an effort is recognized to incorporate power relations into the analysis of environmental conflicts. The emphasis on tackling these conflicts has been placed mostly on economic dimension (capital), generally from an anthropocentric perspective and to that extent, considering “nature” only from the locus of the environment and the imaginary of development. However, in recent decades along with the confluence of the crisis of the modern / colonial-capitalist pattern of power and with the climate crisis/emergency, a new horizon of historical sense has emerged that questions power in all its complexity, both in time and space. These new approaches, the decoloniality of power, solidarity economy, and buen vivir, seek to eradicate the relations of domination and exploitation existing in the central areas of social life, and it is promoted to establish relations of reciprocity and complementarity between humans and with “nature”. The latter from a biocentric perspective, where the ecological becomes meaningful, understood as the recognition of the right of Mother Earth to exist.